1999
DOI: 10.2165/00007256-199928010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Lipoprotein(a)

Abstract: Lipoprotein(a) [Lp(a)] is a unique lipoprotein complex in the blood. At high levels (> 30 mg/dl), Lp(a) is considered an independent risk factor for cardiovascular diseases. Serum Lp(a) levels are largely genetically determined, remain relatively constant within a given individual, and do not appear to be altered by factors known to influence other lipoproteins (e.g. lipid-lowering drugs, dietary modification and change in body mass). Since regular exercise is associated with favourable changes in lipoproteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…The HDL increase in their study was not related to changes in VO 2max but to the total weekly physical activity duration (Sunami et al 1999). We did not observe an effect of physical activity on Lp(a), which is similar to other studies (Hubinger and Mackinnon 1996;Mackinnon and Hubinger 1999). We found differences in Apo-B/Apo-A1 ratio as well as a tendency for a difference in Apo-B concentrations between the protocols, suggesting a minor effect of physical activity on apo-lipoprotein concentration.…”
Section: Discussionsupporting
confidence: 90%
“…The HDL increase in their study was not related to changes in VO 2max but to the total weekly physical activity duration (Sunami et al 1999). We did not observe an effect of physical activity on Lp(a), which is similar to other studies (Hubinger and Mackinnon 1996;Mackinnon and Hubinger 1999). We found differences in Apo-B/Apo-A1 ratio as well as a tendency for a difference in Apo-B concentrations between the protocols, suggesting a minor effect of physical activity on apo-lipoprotein concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Several population and cross-sectional studies showed a lack of association between serum Lp(a) levels and regular moderate physical activity or moderate exercise training. [20][21][22][23][24]29 The few studies that found a beneficial effect of exercise on Lp(a) were either confounded by ethnical issues 25 or included only men. 26 Therefore, it appears likely that the changes in Lp(a) levels observed in our study were caused by the dietary intervention rather than by the increased physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Similarly, the effect of physical exercise on Lp(a) levels is not fully understood, with several contradicting reports. [20][21][22][23][24][25][26][27][28][29] Only few studies were performed in children. 27,28 In this study, we therefore tested the possibility of lowering Lp(a) levels by a weight reduction program during a 3-week dietary camp for obese children.…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of exercise, leading to the reduction of levels of apolipoprotein B, have been widely reported, but this has not been the case with the relationship between exercise and levels of apolipoprotein A-I (57,58). Some authors have found that long-term, regular physical exercise does not seem to modify levels of apolipoproteins in comparison with sedentary groups (59).…”
Section: Cardiovascular Risk Factors and Physical Activitymentioning
confidence: 99%